Reciprocity and Incentive Pay in the Workplace - Robert Dur; Arjan Non; Hein Roelfsema (Tinbergen Institute, 2008)
We study optimal incentive contracts for workers who are reciprocal to management attention. When neither worker's effort nor manager's attention can be contracted, a double moral-hazard problem arises, implying that reciprocal workers should be given weak financial incentives. In a multiple-agent setting, this problem can be resolved using promotion incentives. We test these predictions using German Socio-Economic Panel data. We find that workers who are more reciprocal are significantly more likely to receive promotion incentives, while there is no such relation for individual bonus pay.
Keywords: D86; J41; M51; M52; M54; M55; 330; reciprocity; social exchange; incentive contracts; double moral hazard; GSOEP; Anreizvertrag; Verantwortung; Moral Hazard; Deutschland